2021
DOI: 10.3171/2021.5.focus21220
|View full text |Cite
|
Sign up to set email alerts
|

Augmented reality–assisted roadmaps during periventricular brain surgery

Abstract: Visualizing major periventricular anatomical landmarks intraoperatively during brain tumor removal is a decisive measure toward preserving such structures and thus the patient's postoperative quality of life. The aim of this study was to describe potential standardized preoperative planning using standard landmarks and procedures and to demonstrate the feasibility of using augmented reality (AR) to assist in performing surgery according to these “roadmaps.” The authors have depicted stepwise AR surgical roadma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Of comparative studies, there were 9 retrospective cohort studies, 15 prospective cohort studies and 7 randomised controlled trials (RCTs). Most studies were performed in neurosurgery, 33 general surgery 22 and orthopaedic surgery 14 . Figure 6 shows studies of different designs grouped by authors' surgical specialities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of comparative studies, there were 9 retrospective cohort studies, 15 prospective cohort studies and 7 randomised controlled trials (RCTs). Most studies were performed in neurosurgery, 33 general surgery 22 and orthopaedic surgery 14 . Figure 6 shows studies of different designs grouped by authors' surgical specialities.…”
Section: Resultsmentioning
confidence: 99%
“…Postoperative complications were reported in 13 (6.6%) patients with various tumour types and locations, 27,28 while in six studies patients were reported to be without postoperative complications. [29][30][31][32][33][34] No other data on surgical outcomes were reported in these eight studies, aside from two patients spending two and 6 days in inpatient care following meningioma resection. 27,29 Seven studies of 217 patients-two retrospective cohort studies and five case series-investigated AR in cerebrovascular surgery (see Table A3).…”
Section: Brain Surgerymentioning
confidence: 99%
“…This emerging technology is a tool that will enable us to integrate information and identify and visualize the landmarks previously described for use in pelvic and acetabular surgery. Our anatomical landmarks description and their relationships to different bone areas involved in traumatology can be used to define a “roadmap” in the preoperative planning of an augmented reality (AR) surgery (Bernard et al., 2021; Bernard & Bijlenga, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21] Their results supported the conclusion that VR only moderately affected conventional patient positioning but it did help better detection of pathology-specific anatomic relationships. The use of AR has also been extended to intraoperative visualization of major anatomic landmarks, as documented by Bernard et al, 22 to improve periventricular structure preservation in 13 cases of tumor removal.…”
Section: Discussionmentioning
confidence: 99%